the jurnal ETIKA KOMUNIKASI DALAM AL-QUR’AN MENURUT WAHBAH AZ-ZUHAILI (STUDI MAKNA QAULAN DAN BENTUKNYA): Pendahuluan, Metodologi Penelitian, - Taufiq Hidayatullah (Jurnal Pustaka Cendekia Pendidikan, 2024)
This thesis discusses the ethics of communication in the Qur'an about the meaning of qaulan and its forms. The problem discussed in this study is about the ethics of a person in communicating with others. In today's era, many people who communicate do not prioritize ethics, prioritize their desires in speaking so that communication delivered between individuals does not have meaningful value in the communication. In fact, communication is an urgency for socializing and also to increase high ideals. The Qur'an provides direction or positive values ​​about how to communicate properly and correctly, so that close relationships are created between fellow human beings. To answer this problem, the researcher uses a type of library research by looking for verses with the theme of Qaulan using thematic methods. The primary source is the book of Tafsir al-Munir and the secondary data are books, journals, and those related to this study. The results of this study indicate that Wahbah Az-Zuhaili explains the forms of Qaulan in detail by adjusting the targets faced when invited to communicate. For that, a person in communicating must be based on clear principles.